Transcription activator‐like effector nucleases efficiently disrupt the target gene in Iberian ribbed newts (Pleurodeles waltl), an experimental model animal for regeneration. (11th December 2013) - Hayashi, Toshinori; Sakamoto, Kousuke; Sakuma, Tetsushi; Yokotani, Naoki; Inoue, Takeshi; Kawaguchi, Eri; Agata, Kiyokazu; Yamamoto, Takashi; Takeuchi, Takashi
<x xml:space="preserve">Abstract</x> Regeneration of a lost tissue in an animal is an important issue. Although regenerative studies have a history of research spanning more than a century, the gene functions underlying regulation of the regeneration are mostly unclear. Analysis of knockout animals is a very powerful tool with which to elucidate gene function. Recently, transcription activator‐like effector nucleases (TALENs) have been developed as an effective technique for genome editing. This technique enables gene targeting in amphibians such as newts that were previously impossible. Here we show that newts microinjected with TALEN mRNAs designed for targeting the tyrosinase gene in single‐cell stage embryos revealed an albino phenotype. Sequence analysis revealed that the tyrosinase genes were effectively disrupted in these albino newts. Moreover, precise genome alteration was achieved using TALENs and single strand oligodeoxyribonucleotides. Our results suggest that TALENs are powerful tools for genome editing for regenerative research in newts.